PREVALENCE OF MANGE MITES ON SMALL RUMINANTS IN HARAMAYA WEREDA (DISTRICT), EAST HARARGE ZONE, ETHIOPIA - Nuru, Habib Bedru; Mhatebu, Wubit Tafese (International Journal of Research -GRANTHAALAYAH, 2017)
A cross-sectional study was conducted between November 2011 and March 2012 to determine the prevalence of mange mites and to identify the major mite species affecting small ruminants in Haramaya wereda (district), East Harerghe zone, Eastern Ethiopia. A total of 810 animals from both species (384 sheep and 421 goats) were sampled using the formula of [1]. The study showed that the prevalence of mange mite in sheep and goats was 3.34% and 5.94%, respectively. From 197 and 613, young and adult small ruminants examined for mange mites the recorded prevalence rate was 6.09% and 4.61%, respectively whereas among 373 and 437, male and female small ruminants examined for mange mites the prevalence rate of 4.02 and 5.26% was recorded, respectively. The prevalence rate recorded in lowland and midland was 4.22% and 2.77%, respectively. No statistically significant association was observed between the prevalence rate and different species, age and sex of the animals (p>0.05). However, there was statistically significant association between the prevalence rate of mange infestation and agro-ecological zones (p<0.05). The major species of mites identified were sarcoptes spp, psoroptes spp and demodex spp in goat and only psoroptes spp in sheep. From the mange mite species-affecting goats, sarcoptes scabies was the most prevalent species observed on 4.28% of the goats followed by psoroptes ovis (0.95%) and demodex caprae (0.71%). In sheep, the prevalence of the only identified species, psoroptes ovis was 3.34%. Further studies should be done to evaluate risk factors and the seasonal occurrence of mange in small ruminants in the area to devise effective control measure.